What it takes lessons in the pursuit of excellence - Schwarzman, Stephen A. (New York Simon & Schuster, Inc, 2019)
People know who Stephen Schwarzman is -- at least they think they do. He's the man who took
Includes index.
Keywords: Schwarzman, Stephen A., 1947-